Increasing Early Awareness of Hazard of Children with ADHD’s ODD and Aggression by Structural Equation Modeling (SEM) - Tzang, Ruu-Fen; Chang, Chuan-Hsin; Chang, Yue-Cune (International Journal of Statistics in Medical Research, 2014)
Background: The hazard of children with Attention Deficit Hyperactivity Disorder (ADHD) occurring Oppositional Defiant Disorder (ODD) (shorten as ADHD’s ODD) and aggression is not well understood. This study employs structural equation modeling (SEM) to operationalize aggression as joined symptoms on children with ADHD’s ODD by analyzing how aggression symptom transact the symptom severity of ADHD’s ODD. Methods: ADHD children and adolescents received clinical diagnosis and inattention (ADHD-I), hyperactivity/impulsivity (ADHD-H/I), and ODD subscale of Swanson, Nolan, and Pelham, version IV scale (SNAP-IV-C) and child behaviour check list (CBCL). SEM was applied to associate ADHD-I, ADHD-H/I, and ODD subscale toaggression. Results: Significantly aggressive symptom on CBCL interact with symptom of ADHD, ODD on SNAP; the standardized direct effect of ADHD symptom by SNAP on behavior symptom by CBCL is 0.57 and the standardized total (direct and indirect) effect of ODD symptom on behavior symptom is 0.34. Children with ADHD’s ODD symptom share similar characteristic symptom as symptom of ADHD children with deficient emotional self-regulation (DESR). The aggression is highly correlated with ODD (0.607). Conclusions: On ADHD symptom, the likelihood of symptom severity is predicted by the symptom of ADHD-I, ADHD-H/I, and ODD. On ODD symptom, ODD is associated with aggression and anxiety/depression symptom. There is a need to regard child with symptom of ADHD’s ODD and aggression as a child with heavy genetic loading and predictor of disruptive behavior disorder.